2015
DOI: 10.2474/trol.10.115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Verification of Impact Response on Air Thrust Bearing with Topological Optimized Groove

Abstract: This paper describes experimental and theoretical verification in impact response of optimized grooved bearing designed by topological optimization. Firstly, in order to measure the impact response characteristics accurately temperature compensation method for air film thickness of bearing is proposed and confirmed by experiment of bearing reaction force with air film thickness. Then, in this study, impact experiments were conducted with the optimized bearing and spiral grooved bearing and compared with theori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The phase transformation characteristics and model parameter should be considered in the simulation model. Then, the changes of lubricant parameters (density, viscosity and thermal conductivity) should be considered in the simulation [3][4][5]. Then, a second critical difficulty is how to show the correlation properties between structural parameters and lubricant characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The phase transformation characteristics and model parameter should be considered in the simulation model. Then, the changes of lubricant parameters (density, viscosity and thermal conductivity) should be considered in the simulation [3][4][5]. Then, a second critical difficulty is how to show the correlation properties between structural parameters and lubricant characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results was not only a demonstration for the proposed method but also illustrated the influence of groove shape on the load carrying capacity of thrust bearing. For the optimum design problem of thrust bearing, Masayuki et al [22,23] established a hydrodynamic analysis model of gas-lubricated thrust bear-ing considering the angular displacement characteristics, and a new groove shape was obtained, which included two curved portions. Wu et al [24] extended a new CFD model for researching the hydrodynamic response in the grooved two-disc system.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement of dynamic variation of air films was realized. Many researches [11][12][13][14] have shown that the film thickness from 3 μm to 50 μm was a general working clearance for most gas lubricated devices. What is more, a large film thickness is required for dynamic loads to reduce the possibility of contact.…”
mentioning
confidence: 99%